Living in grace through the holy Mysteries. The relationship between grace and freedom - Petrov, George Daniel; Zagan, Andrei-Dragoș; Fofiu, Gheorghe Adrian (Technium Social Sciences Journal, 2022)
The uncreated divine grace is one of the most important chapters for Orthodox theology, because the progress of the human person towards the Absolute depends on its correct understanding. Man is not created to be limited by the standards of materiality, his aspiration is always to the Living, Personal, Absolute God in whom he can find rest. Without man’s participation in the communion with the Creator, a communion that is achieved in grace, he comes from nowhere and goes to nowhere, in the sense that the aspiration to the Absolute cannot be deceived by anything from the materiality of the world.